Assessing the Adequacy of a Defined Contribution Retirement Plan: An Actuarial Analysis of Income Replacement Ratios - Sa’at, Aimi Syairah Md; Shair, Syazreen Niza; Lazam, Norazliani Md (Journal of Quality Measurement and Analysis, 2026)
This study proposes a method for estimating optimal contribution rates for a defined contribution (DC) retirement plan by incorporating uncertainties to ensure income adequacy for retirees. The replacement ratio, representing post-retirement income as a proportion of the final salary, serves as the key indicator of adequacy. The study assesses the impacts of interest rates and mortality uncertainties on the replacement ratio, with findings constrained to the specified set of uncertainty indicators under consideration. The Entry Age Normal (EAN) method allocates the present value of future benefits as a level percentage of salary from entry age to retirement, while the actuarial present value framework is used to determine the value of retirement annuity benefits. Using the equivalence principle, the study calculates the annual retirement income and replacement ratio. Results show that while higher interest rates and investment returns increase the replacement ratio, restricting lump-sum withdrawals between 55 and 60 can further enhance income adequacy. The study proposes gender- and age-specific contribution rates to ensure sufficient retirement income. Finally, the study assesses the financial sustainability of retirees using the optimal contribution rates in the context of Malaysia's median annual salary.